Transforming Food Consumption: Impact of an Educational Intervention on Adolescent Girls' Diets (2024)
ABSTRACT: Introduction: Adequate nutrient intake and diet quality in adolescents are crucial for their development and the prevention of noncommunicable chronic diseases. Objective: To compare nutrient intake and diet quality in a group of adolescent girls before and after an educational intervention. Methods: A case-control study was conducted with 96 adolescents selected from a total of 1010 participants. The adolescents were divided into two groups: 48 participated in the intervention, and 48 did not; they were matched by age and community. Pre-test and post-test assessments were conducted to evaluate changes in knowledge and practices, and the 24-hour recall method (R24h) was used to assess the Global Diet Quality Score (GDQS) before and after the educational intervention named CERES School. Statistical tests such as the Wilcoxon signed-rank test, MannWhitney U test, paired and independent t-tests, and a multivariate linear regression model controlling for variables such as age, socioeconomic status, and physical activity were applied. Results: The pre- and post-analysis revealed a significant acquisition of knowledge that favored decision-making in food purchase, selection, and preparation, increased daily water consumption, inclusion of nutrient-dense foods, reduction in the consumption of ultra-processed foods, and recognition of the nutritional value of fruits, vegetables, legumes, and dairy groups. A significant increase in the intake of energy, protein, fats, fiber, calcium, zinc, and various vitamins (A, B2, B3, B9, and C) was observed. Additionally, there was an increase in the consumption of fruits, vegetables, legumes, and fat-rich dairy products, and a decrease in the consumption of sweets and ice cream, improving the average GDQS scores. The educational intervention improved the total GDQS by 33%, controlling socioeconomic status, body self-perception, and physical activity. Conclusions: The CERES School educational intervention achieved significant changes in nutrient intake and healthy food consumption, as reflected in the improvement of the GDQS. Conflicts of Interest: none